2022
DOI: 10.30541/v40i1pp.1-25
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Productivity Growth Differential in Punjab, Pakistan: A District-level Analysis

Abstract: The results of this paper show that the crop output increased at the rate of 2.6 percent per annum, dominated by the share of TFP growth. Wide variation exists among cropping systems as well as within the system both in TFP growth and output growth. The mungbean zone emerged as a leader in TFP growth with 3.6 percent per annum, followed by barani (3.2 percent), cotton (1.9 percent), mixed (1.1 percent), and rice (1.0 percent) zones. Rice, mixed, and cotton zones show a negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 29 publications
(29 reference statements)
1
4
0
Order By: Relevance
“…The estimated elasticities of land (the fifth RHS variable) for all attempted specifications have been negative and insignificant. The implied zero elasticity of land conforms to recent empirical evidence[Ali and Byerlee (2000) andAhmad (2001)], which indicates strongly towards the prevalence of a land degradation phenomenon in Pakistan. Given the intractability of a zero input coefficient in the CD model, the land input variable has been dropped from the production function for further model estimation.…”
supporting
confidence: 87%
“…The estimated elasticities of land (the fifth RHS variable) for all attempted specifications have been negative and insignificant. The implied zero elasticity of land conforms to recent empirical evidence[Ali and Byerlee (2000) andAhmad (2001)], which indicates strongly towards the prevalence of a land degradation phenomenon in Pakistan. Given the intractability of a zero input coefficient in the CD model, the land input variable has been dropped from the production function for further model estimation.…”
supporting
confidence: 87%
“…Another study conducted by Khan et al (2020) [29] in Pakistan revealed that climate change-induced the loss of wheat and rice productivity by 2050 to be 19.5 billion dollars on Pakistan's Real Gross Domestic Product. The study performed by Ahmad et al (2014) [30] would reduce the wheat yield by 7.4 percent due to an increase in mean temperature of 1 • C during the sowing time in Pakistan.…”
Section: Panel Data Regression Modelmentioning
confidence: 99%
“…Ahmad et al ( 2014 ) evaluated the effect of climatic change on productivity of wheat in Pakistan, using data from 1981 to 2010 on the district level. Production function was used for data analysis purposes.…”
Section: Introductionmentioning
confidence: 99%